Association between pretransfer cleavage-stage blastomere dynamics and pregnancy outcomes in fresh single embryo transfer cycles: a retrospective cohort study - Wang, Qingkai; Geng, Shuangshuang; Feng, Hansheng; Zhang, Bin; Deng, Kai; Zhao, Zimo; Xu, Jinfeng; Wang, Haiye; Wang, Jing; Yang, Weimin; Cai, Liyi (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the impact of embryo blastomere cell number and dynamic changes in cell number during the morning of embryo transfer day (7:00–11:00) on clinical pregnancy outcomes in fresh single embryo transfer (SET) cycles.MethodsA retrospective cohort study was performed, including 561 fresh SET cycles conducted between January 2022 and June 2024. Cycles were categorized into four groups based on embryo blastomere count before transfer: ≤7-cell, 8-cell, 9–10-cell, and ≥11-cell groups. We analyzed the relationship between the increase in blastomere number observed from 7:00 a.m. to 11:00 a.m. on the day of transfer and clinical pregnancy outcomes. Multivariate logistic regression analysis was utilized to assess the influence of various factors on clinical pregnancy and live birth rates.ResultsClinical pregnancy rates significantly differed among the ≤7-cell, 8-cell, 9–10-cell, and ≥11-cell groups (10.64%, 36.69%, 42.31%, and 46.32%, respectively; P = 0.004). Live birth and biochemical pregnancy rates exhibited a similar increasing trend with higher cell numbers (P = 0.001), whereas early miscarriage rates showed no significant differences among groups (P = 0.157). In the 9–10-cell group, embryos that exhibited an increase in blastomere number had significantly higher clinical pregnancy rates (50% vs. 23.68%, P = 0.006) and live birth rates (41.30% vs. 15.79%, P = 0.005). No significant differences were observed in the ≤7-cell and 8-cell groups (P > 0.05). Multivariate logistic regression analysis demonstrated that increased endometrial thickness significantly improved clinical pregnancy likelihood (P = 0.034), whereas lower blastomere number (≤7-cell) significantly reduced clinical pregnancy rates (P = 0.002).ConclusionA higher embryo blastomere count before transfer is significantly associated with improved clinical pregnancy and live birth outcomes in fresh SET cycles. Short-term increases in blastomere number on the morning of transfer day may reflect superior embryo developmental potential.